EFFECTIVENESS OF THE SCHOOL OF GYMNASTICS IN 7 YEARS OLD CHILDREN - Zoran Čuljak; Mile Ćavar; Damir Crnjac; Kristijan Marić; Marin Ćorluka (Sport Scientific And Practical Aspects, 2025)
The aim of this study is to determine the influence of treatment in school of gymnastics on certain motor abilities in seven-year-old boys and girls. Subjects were divided into two groups: experimental group (EG, 17 boys, 18 girls) and control group (CG, 17 boys, 20 girls). Beside regular classes of Physical education (PE) EG attended additional sport-school with gymnastics program, three training units a week for 60 minutes in a period of six months. The CG was not actively involved in extracurricular physical activity. Univariate analysis of variance has shown that experimental treatment causes positive changes in motor abilities of seven- year- old boys and girls. When it comes to boys, a significant improvement of explosive strength, dynamic and static muscular endurance, frequency of movement and flexibility was gained in EG. Girls EG improved explosive strength, dynamic and static muscular endurance, frequency of movement, balance and flexibility. CG of each gender improved only dynamic muscular endurance. There was no significant improvement of coordination in both EG which was unexpected.